The Moral Dimensions of Teaching : Language, Power, and Culture in Classroom Interaction. - Buzzelli, Cary (Taylor and Francis, 2014)
Cary Buzzelli and Bill Johnson reinvigorate the enduring question: What is the place of morality in the classroom? Departing from notions of a morality that can only be abstract and absolute, these authors ground their investigation in analyses of actual teacher-student interactions. This approach illuminates the ways in which language, power and culture impact ""the moral"" in teaching. Buzzelli and Johnson's study addresses a wide range of moral issues in various classroom contexts. Its practical and diverse examples make it a valuable resource for teachers and teacher development programs.